ASPECTS OF USING VISUAL ART IN PROTEST EXPRESSION THROUGH ACTS OF DIRECT ACTION - Sabakar, Sergii (Theory and practice of design, 2025)
Purpose of the research study is to analyse the role of the visual arts as a means of expressing protest through direct action and activism. The research aims to examine contemporary examples of the use of graffiti, performance, etc. as a means of mobilising, creating alternative narratives and communicating socio-political messages. Methodology. The thesis adopts a comprehensive methodological approach, combining several scholarly methods for an in-depth analysis of visual activism. In particular, a systematic and structural analysis of a wide range of multimedia sources was carried out, which allowed us to identify the main elements and patterns of protest art formation. In addition, a comparative case study analysis was used to examine historical and contemporary examples of protest practices in different cultural and political contexts. The method of content analysis was also used to study visual images and symbols used in public space and on the Internet. Results. The study shows that visual art is a powerful tool for mobilisation and non-violent resistance, capable of transforming public space and creating alternative forms of communication. An analysis of examples of contemporary protest movements shows the universality of artistic means in conveying emotional ideas and shaping collective consciousness. The scientific novelty of the study lies in a comprehensive analysis of visual art as a means of direct action within contemporary protest movements. This analysis covers a wide range of visual activism practices and socio-political statements in the twenty-first century. Particular attention is paid to the Ukrainian experience, including examples of artistic resistance during the Revolution of Dignity and the subsequent large-scale war, and the role of art in non-violent resistance. Practical relevance of the study lies in the possibility of applying the results obtained in artistic and educational practice, particularly in higher art education curricula focused on developing socially critical thinking. Additionally, the study could inform the work of human rights organisations that utilise art as a tool for public communication and human rights advocacy.